Synthesis and Photocatalytic Properties of Reduced Graphene Oxides Loaded-nano ZnS/CuS Heterostructures - ZENG Bin; CHEN Xiao-hua; WANG Ci-rong (Cailiao gongcheng, 2017)
The reduced graphene oxides(rGO) loaded-nano ZnS nanoparticles were fabricated by microwave heating method and by ion exchanged reaction reduced graphene oxides(rGO) loaded-nano ZnS/CuS heterostructures were obtained. The structure, morphology were characterized via scanning electron microscopy(SEM), transmission electron microscopy(TEM) and X-ray diffraction pattern(XRD). The effect of the mass fraction of graphene oxides, sulfur source and microwave heating time on the morphology and photocatalyitc performance were discussed. The results show that graphene uniformly loaded-nano ZnS/CuS heterostructures are obtained on the condition of graphene mass fraction of 10%, thioacetamide acting as sulfur source, microwave heating time is 30min. rGO-loaded nano ZnS/CuS heterostructures nanoparticles enhance photocatalytic performance with 81.2% decomposition of MO in 150min under visible light, demonstrating the excellent photocatalytic performance. The high visible photocatalytic performances are attributed to photoinduced interfacial charge transfer in the nano heterostructures and their further separation and transfer by rGO.